Pureza [motion picture] the story of Negros sugar - Abello, J. (Negros Pureza and Bonfire Productions, Inc., 2012)
No Sugar coating. Pureza: The sotry is Negros Sugar is a full-lenght documentary film on the struggling sugar industry of the island of Negros in the Philippines and how a piece of cryatallized grain could affect a whole island of 2.7 million people.